?RETENTION OF NUTRITIONAL QUALITY OF SOYBEAN DURING EXTRUSION COOKING (Biological Sciences - PJSIR, 2003)
Trypsin inhibitor (TI) is one of the major anti-nutritional components of soybean and must be inactivated before its protein content can be safely and efficiently utilized for food and feed purposes. However, retention of the protein quality is also a prime consideration while inactivating TI. This research was conducted to study the effect of extrusion process conditions (temperature, screw speed and moisture content) on trypsin inhibitor activity (TIA) and nitrogen solubility index (NSI) and to develop a model for prediction of TI inactivation during extrusion cooking based on its reaction kinetics. A laboratory size single screw extruder was used for extrusion cooking of full-fat soybean implement- ing a (4x4x4)x2 full factorial design. TIA was measured using a standard procedure and NSI by AACC procedure. The reaction rate constant for loss of TIA was calculated based on its activation energy from literature and experimental TIA data. The statistical models correlating product temperature with operating conditions and activation energy were combined with mathematical equations for predicting TIA during the cooking process. TIA and NSI of the soybean (William 82 variety) were found to be 47.0 TIU mg-1 and 78% respectively. Trypsin inhibitor inactivation ranged from 90% of that of raw soybean at low screw speed (75 rpm) and high barrel temperature (170°C) (LSHT) to 50% for higher screw speed (150 rpm) and low barrel temperature (140°C) (HSLT). Reduction in NSI for similar extrusion conditions ranged from 95% at LSHT to 50% at HSLT of that of raw soybeans. Variations between predicted and measured TIA values were less than 1% for the given conditions. Results indicated that reduction in TIA and NSI occurred mainly in the compression and metering sections of the extruder and that they paralleled each other, thereby making it difficult to retain high NSI while inactivating TI. However, the efficiency of extrusion cooking for TI inactivation has been proved. The model can be used for determining optimum conditions for extrusion cooking of soybean for food and feed purposes.